The role of tonic immobility and control in the development of intrusive memories after experimental trauma. Issue 6 (3rd July 2019) - Kuiling, J. M. E.; Klaassen, F.; Hagenaars, M. A.
ABSTRACT: Tonic immobility (TI; state of motor inhibition during threat) has been implicated in the onset of intrusive trauma memories, while controllability was associated with reduced anxiety. The present study investigated the interaction between TI and control in the development of intrusive memories of an analogue trauma. Sixty-four participants watched negative pictures while being allowed to close their eyes (InControl) or not (NoControl). They completed measures for spontaneous TI afterwards and recorded intrusive memories of the pictures in a diary in the subsequent week. Bayesian analyses were used to test informative hypotheses. Spontaneous TI during picture viewing was positively associated with increased intrusion frequency. Intrusion frequency did not differ for InControl versus NoControl. Moderation (control x TI) and non-moderation (main effect of TI only) were both adequate models, with no preference. Our results confirm the importance of TI in PTSD development. Implications of the findings regarding control merit more research.